Uso de etileno no desverdecimento da tangerina Poncã produzida nas regiões Norte e Zona da Mata de Minas Gerais. - Costa, Marcio Gama dos Santos da (2009)
The objective of this work was to promote the degreening, without losing internal fruit quality, of Poncã tangerine from two regions of Minas Gerais. Two experiments were carried out. In the first, the fruits were harvested from a commercial orchard in the northern region, and the second experiment used fruits from Zona da Mata. Fruits were harvested when showing minimum attributes of 35% juice, 9° Brix and soluble solids/tritable acidity ratio of 9.5. Then the fruits were packed in airtight boxes, which were exposed for 24, 48 and 96 h to different concentrations of ethylene gas: 0, 5, 10, 20 and 40 μL.L-1, at 20 + 1 °C and 90 + 5% relative humidity, respectively. Every 24 h, the boxes were opened for renewal of internal atmosphere, by reapplying the gas until treatment end. A post-treatment phase of 96 h duration took place at the end of each exposure time, when the fruits were kept in ethylene-free atmosphere, in cold chamber, at the same temperature and relative humidity used during the exposure to ethylene. During this phase, the fruits were evaluated every 24 h, and the difference in skin color, Hue angle of the peel, total chlorophyll and carotenoid content, soluble solids content, tritable acidity and SS/TA ratio of juice, solute leakage, CO2 production and loss of fruit fresh mass. In the first experiment, the fruits showed stronger degreening with increasing time of exposure to ethylene, most markedly for 96 h. After this exposure time, the Hue angle increased from 96.1o, in the first assessment days, to 82.3o, at the end of 96 h, which was lower than values observed in naturally degreened fruits. Fruits exposed for 24 h showed evolution of the yellow peel color similar to the untreated ones. It was observed that fruits left to ripe on the plant showed non-homogeneous peel degreening. The fruits exposed to ethylene for 96 h showed no visual signs of loss of commercial quality, although there was increased solute leakage from the peel during the treatment. Soluble solids content, tritable acidity and SS/TA ratio remained unchanged throughout the assessment period. The synthesis of total carotenoids in the peel was low, from 6.0 μg/cm2, in control fruits at the end of evaluations, to a maximum of 8.2 μg/cm2, in fruits exposed to ethylene for 96 h. This synthesis was insufficient to reach the orange color, therefore, the degreening of fruit peel was due, almost exclusively, to chlorophyll degradation. In the second experiment, the fruits showed yellowing of the peel stronger than fruits of the first experiment. The exposure time of 96 h proved to be the most efficient in promoting the fruit degreening in comparison with other times. Color evolution was quite similar between the control and fruits treated for 24 and 48 h. Fruits of all treatments had very low synthesis of total carotenoids in the peel, changing from 7.3 μg/cm2 in control fruits to 9.2 μg/cm2, maximum value observed in fruits exposed to ethylene for 96 h. Even in fruits showing the strongest yellowing, there was little participation of new synthesized carotenoids in the composition of the final color. Fruits fully developed in the plant reached the maximum degreening, becoming orange, the typical color of the species. Thus, for fruits produced in the Zona da Mata region, the post-harvest degreening with ethylene is only justified to anticipate the harvest, since the region has favorable climate to natural degreening. However, for fruits produced in northern Minas Gerais, where the high temperatures prevailing throughout the year impair the natural degreening, the postharvest use of ethylene may serve to obtain a more uniform peel color.